BEAMFORMING UNIT FOR SUB-ARRAY OF DECAMETER AND METER WAVE RADIO TELESCOPE GURT - Yerin, S. N.; Tokarsky, P. L.; Gridin, A. A.; Bubnov, I. N.; Konovalenko, A. A.; Falkovich, I. S.; Reznik, A. P. (Видавничий дім «Академперіодика», 2014)
A beamforming device for a 5×5-element subarray of receiving phased antenna array of new GURT radio telescope designed to operate within 10 − 70 MHz is presented. The device is composed of six identical units. Each unit contains equal-arm 5:1 combiner with connected to its arms discrete phase shifters based on time delay lines switching principle. Five of these units combine the signals of array elements inside rows of the subarray, whereas the sixth one assembles the combined signals of subarray rows. Operation principle of beamforming unit is described, the results of its computer modeling and performance measurement results are given. The time-delay lines manufacturing errors influence on subarray power parameters is estimated, as well as their fabrication tolerance found.Key words:  phase changer, beamformer, phased array, radio-telescopeManuscript submitted 24.04.2014Radio phys. radio astron. 2014, 19(3): 240-248 REFERENCES1. KONOVALENKO, A. A., 2005. Low-Frequency Radio Astronomy Prospects. Radio Phys. Radio Astron. vol. 10, special issue, pp. S86–S114 (in Russian) 2. MYLOSTNA, K. Y. and ZAKHARENKO, V. V., 2013.Search and Study of Storm Activity on Saturn and Other Planets of the Solar System. Radio Phys. Radio Astron. vol. 18, no. 1, pp. 12–25 (in Russian). 3. DE VOS, M., GUNST, A. W., and NIJBOER, R., 2009.The LOFAR Telescope: System Architecture and Signal Processing. IEEE Proc. vol. 97, Is. 8, pp. 1431–1437. DOI: https://doi.org/10.1109/JPROC.2009.2020509Source 4. ELLINGSON, S. W., CLARKE, T. E., COHEN, A., CRAIG, J., KASSIM, N. E., PIHLSTROM, Y., RICKARD, L. J., and TAYLOR, G. B., 2009. The Long Wavelength Array. IEEE Proc. vol. 97, is. 8, pp. 1421–1430. DOI: https://doi.org/10.1109/JPROC.2009.2015683 5. GIRARD, J. N., ZARKA, P., TAGGER, M., DENIS, L., CHARRIER, D.,KONOVALENKO, A. A., and BOONE, F., 2012. Antenna design and distribution of the LOFAR super station. Comptes Rendus Physique. vol. 13, Is. 1, pp. 33–37. 6. DEWDNEY, P. E., HALL, P. J., SCHILIZZI, R. T., and LAZIO, T. J. L. W., 2009. The Square Kilometre Array. IEEE Proc. vol. 97, is. 8, pp. 1482–1496 7. KONOVALENKO, A. A., FALKOVICH, I. S., GRIDIN, A. A., TOKARSKY, P. L., and YERIN, S. N., 2012. UWB active antenna array for low frequency radio astronomy. In: Proc. of the VI-thIntern. Conf. on Ultrawide band and Ultrashort Impulse Signals (UWBUSIS'12). Sevastopol (Ukraine). pp. 39–43. DOI: https://doi.org/10.1109/UWBUSIS.2012.6379725 8. BRUCK, Y. M. and INYUTIN, G. A., 1978. Binary digital delay line (phase shifters) for electrically controlled broadband antenna. In: Anteny. Moscow, USSR: Svyaz' Publ., no. 26, pp. 107–121 (in Russian). 9. BRAUDE, S. Y., MEGN, A. V. and SODIN, L. G., 1978. Decameter wave band radio telescope UTR-2. In: Anteny. Moscow, USSR: Svyaz' Publ. no. 26, pp. 3–15 (in Russian). 10. FALKOVICH, I. S., KONOVALENKO, A. A., GRIDIN,A. A., SODIN, L. G., BUBNOV, I. N., KALINI CHENKO, N. N., RASHKOVSKII, S. L., MUKHA, D. V.and TOKARSKY, P. L., 2011. Wide-band high linearity active dipole for low frequency radio astronomy. Exp. Astron.vol. 32, is. 2, pp. 127–145. DOI: https://doi.org/10.1007/s10686-011-9256-z 11. VOSKRESENSKII, D. I., STEPANENKO, V. S., and FILIPPOV, V. S. Microwave devices and antennas. Designing phased arrays. Moscow: Radiotekhnika Publ. (in Russian). 12. Surface-mounting, 1-GHz-Band / 3-GHz-Band, Miniature, DPDT, High-frequency Relay datasheet [online]. Available from:www.omron.com/ecb/products/pdf/en-g6k_2f_rf.pdf. 13. Surface Mount Power Splitter/Combiner SCP-5-1 datasheet [online]. Available from: www.minicircuits.com/pdfs/SCP-5-1.pdf. 14. SHIFRIN, Ya. S., 1970. Questions of statistical antenna theory. Moscow: Sov. radio. Publ. (in Russian). 15. INDENBOM, M. V., 2008. Fluctuations of the directivity pattern of the antenna array for output. Anteny, no. 4, pp. 40–46. 16. MERKULOV, V. V., 1966. By the estimation of emitters CPV system with phase and amplitude distortion. Radiotechnika i elektronika, vol. 11, no. 11, pp. 2066–2069. 17. STEBLIN, V. I. and KLASSEN, V. I., 1981. The method of analysis of statistical characteristics of CPV phased array antenna with random amplitudes and phases of the location of radiators. Radiotechnika i elektronika, vol. 26, no. 3, pp. 524–531. 18. SHIFRIN, Ya. S. and KORNIENKO, L. G., 2000. Statistics field antenna arrays. Anteny, no. 1, pp. 3-26. 19. SAZONOV, D. M., GRIDIN, A. N., and MISHUSTIN, B. A., 1981. Microwave devices. Moscow: Vyshchaya shkola Publ. (in Russian).